Prevalence of methicillin-resistant Staphylococcus aureus colonization in individuals from the community in the city of Sao Paulo, Brazil - Taniela Marli Bes; Roberta Ruedas Martins; Lauro Perdigão; Diego Mongelos; Luisa Moreno; Andrea Moreno; Gerson Salvador de Oliveira; Silvia Figueiredo Costa; Anna Sara Levin (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
ABSTRACT Staphylococcus aureus (SA) is a commensal habitant of nasal cavities and skin. Colonization by community-acquired methicillin-resistant SA (CA-MRSA) is associated with infections in patients who have not been recently hospitalized. The aim of this study is to determine the prevalence of MRSA colonization in an outpatient population, currently unknown in Brazil. Three-hundred patients or caregivers from two teaching hospitals were included. A questionnaire was applied and nasal swabs were obtained from patients. Swabs were inoculated in brain heart infusion (BHI) with 2.5% NaCl and seeded in mannitol. Suspicious colonies were subjected to MALDI-TOF MS Microflex™ identification. Antimicrobial susceptibility test for oxacillin was performed for SA-positive samples by microdilution. Polymerase chain-reactions for detection of mecA and coA genes were performed for resistant samples. Data about MRSA carriers were compared with non-carriers. There were 127 S. aureus isolates, confirmed by MALDI-TOF. Only seven (2.3%) were MRSA and positive for mecA and coA genes. Factors associated with MRSA carriage were African ethnicity, skin diseases or antibiotic use. The majority of them were from Dermatology clinics. Prevalence of MRSA colonization in individuals from the community was low in our study (2.3%). This finding raises the hypothesis of inter-household transmission of SA, although we did not find any association between MRSA-colonization and the shared use of personal objects. Given the low prevalence of MRSA carriers observed, empirical antimicrobial coverage for MRSA in community-acquired infections should be not necessary.